Desenvolvimento e caracterização de alimentos isentos de glúten contendo farinha de grãos integrais como fonte de nutrientes essenciais - Gohara, Aline Kirie (2016)
Cake is the second most consumed food among the bakery ones, the first product is bread. This popularity is mainly due to convenience and sensory acceptance. However, one negative point of this food is the lack of essential nutrients for human beings. This problem is worse in gluten-free products because the main ingredient used by bakery industries is rice flour, which consists basically of carbohydrates. Azuki (Vigna angularis) is a legume widely produced and consumed in Asia, used in the various products manufacturing, especially in typical sweets. Chia (Salvia hispanica L.) is an angiosperm plant from the mint family (Lamiaceae) characterized as a grain from tropical and subtropical climate, widely consumed in pre-Columbian America by the Aztecs, in the region that includes Mexico and Guatemala. Both grains, azuki and chia, are considered rich source of many essential nutrients to good health maintenance. One of the most relevant aspects regard to nutrients is the lipid composition. Several fatty acids are essential for the maintenance of biological systems, mainly the ones from n-3 series. Factorial design allows a smaller number of experiments and findings from qualitative results. Principal Component Analysis (PCA) allows the standard recognition, information is feasible and there is a reduction in the dimensionality of the data. Desirability analysis allows the detection of the optimum region. ARTICLE 1: The objective of this work was the application of chemometric methods to investigate the influence of the factors: percentage of chia and azuki flours on lipid composition and nutritional aspects of gluten-free chocolate cakes. ARTICLE 2: This work aimed at evaluating angularis and niponensis cultivars of azuki beans from south region of Brazil. ARTICLE 1: A 22 full factorial design (two factors at two levels) with center point in quintuplicate was conducted to investigate the influence of factors: % of chia and azuki flours on the lipid composition of gluten-free chocolate cake. Mathematical models were proposed to the responses, as well as principal component analysis and evaluation of the desirability function. ARTICLE 1: Adzuki beans (Vigna angularis) cultivars: angularis and niponensis, were acquired directly from the producer in the region of Maringa city, Parana state, Brazil. Both cultivars were evaluated concerning proximal composition and crude energy, fatty acid composition, indices of the nutritional quality of lipids, tocopherol isomers, vitamin E activity, minerals, dietary reference intake values, bioactive properties, and multivariate analysis. ARTICLE 1: The factors % of chia and azuki flours were significant, but chia flour presented higher influence on the results. The increasing of these values contributed to improve the fatty acid composition, Increased values of both factors contributed to improve contents of polyunsaturated fatty acids, mainly n-3 series, and provided more adequate nutritional indexes. The principal component analysis distinguished the samples with higher contents of chia and the desirability analysis indicated the sample with the highest level of chia as the optimal region. ARTICLE 2: Both cultivars presented proximal composition similar to literature and the majority fatty acids were 18:2n-6, 16:0 and 18:3n-3. All samples showed polyunsatured fatty acids prevalence and nutritional indices and ratios considered adequate for biological system maintenance of a healthy organism. The grains presented significant contents of tocopherols and vitamin E activity, resulting in a high contribution to the dietary reference intake. Significant contents of iron, manganese and zinc were also found in the azuki beans, and they are very important mainly due to their function as cofactors in metabolic reactions. Phenolic compounds and flavonoids corroborated with other studies and contributed to the antioxidant activity. The principal components multivariate analysis allowed distinguishing the cultivars, and the two principal components could explain 92.28% of data variance. ARTICLE 1: Chemometric methods were very useful for improvement of fatty acids composition of gluten-free chocolate cake. The models analyzed were significant and allowed obtaining the response surfaces. The formulation with higher contents of chia and azuki flour was considered as a point of greatest desirability. The addition of chia and azuki flours in gluten-free products is a great alternative to improve nutritional characteristics of foods, mainly bakery ones that can be consumed even by celiac patients. ARTICLE 2: Cultivars of adzuki beans are excellent sources of many essential compounds, such as essential fatty acids, tocopherols, minerals and antioxidant properties The multivariate analysis allowed distinguishing batches of angularis and niponensis cultivars, as well as evaluating the importance of the parameters. The traditional use of adzuki beans in the eastern dietary is promising due to their intrinsic characteristics.